Transformation of Inhibitor of Meristem Activity (IMA) Gene into Jatropha curcas L. - Paserang, Asri Pirade; Tjahjoleksono, Aris; Widyastuti, Utut; Suharsono, (UI Scholars Hub, 2015)
Jatropha is one of the many biodiesel plants developed in tropical countries. Efforts to increase its productivity can be done using various methods of breeding. One of the breeding methods is the introduction of genes into the Jatropha plant. The aim of this study is to assess the success of genetic transformation using the Inhibitor of Meristem Activity (IMA) gene in Jatropha curcas. The research procedures included inoculation of explants with Agrobacterium tumefaciens, callus induction, screening test of selection media, regeneration, and gene expression analysis using Polymerase Chain Reaction (PCR). IMA is one of the genes that controls flowering genes and ovule development. It was first isolated from tomato plants and has been successfully overexpressed in these plants using the Cauliflower Mosaic Virus (CaMV) 35S promoter. In this experiment, plant transformation was performed on J. curcas as the target. Explant callus formation in both the control and treated samples was good, but shoot formation decreased dramatically in the treated explants. PCR analysis indicated that IMA genes can be inserted into J. curcas with the size of the IMA gene is 500 bp.